Cloning, purification, crystallization and preliminary X-ray analysis of the receiver domain of the histidine kinase CKI1 from Arabidopsis thaliana - Klumpler, Tomás; Pekárová, Blanka; Marek, Jaromír; Borkovcová, Petra; Janda, Lubomír; Hejátko, Jan (Acta crystallographica. Section F, Structural biology and crystallization communications, 2009)
The receiver domain (RD) of a sensor histidine kinase (HK) catalyses the transphosphorylation reaction during the action of HKs in hormonal and abiotic signalling in plants. Crystals of the recombinant RD of the Arabidopsis thaliana HK CYTOKININ-INDEPENDENT1 (CKI1(RD)) have been obtained by the hanging-drop vapour-diffusion method using ammonium sulfate as a precipitant and glycerol as a cryoprotectant. The crystals diffracted to approximately 2.4 A resolution on beamline BW7B of the DORIS-III storage ring. The diffraction improved significantly after the use of a non-aqueous cryoprotectant. Crystals soaked in Paratone-N diffracted to at least 2.0 A resolution on beamline BW7B and their mosaicity decreased more than tenfold. The crystals belonged to space group C222(1), with unit-cell parameters a = 54.46, b = 99.82, c = 79.94 A. Assuming the presence of one molecule of the protein in the asymmetric unit gives a Matthews coefficient V(M) of 2.33 A(3) Da(-1). A molecular-replacement solution has been obtained and structure refinement is in progress.
Keywords: proteiny huseníčku; Protein Kinases; Arabidopsis; klonování DNA; Crystallization; krystalizace; Crystallography, X-Ray; proteinkinasy; Arabidopsis Proteins; histidinkinasa; Cloning, Molecular; Histidine Kinase; krystalografie rentgenová